2018
DOI: 10.26554/sti.2018.3.1.7-13
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity Test of Ethanolic Seri Leave’s (Muntingia Calabura L.) Extract in Male Rats Induced by Alloxan

Abstract: Antidiabetic activity test of ethanol extract of seri leave (Muntingia calabura L.) rats induced by alloxan has been done. Male wistar albino rats are used as animal models which divided into 6 groups, normal group (aquadest), negative control group (Na CMC 0,5%), positive control group (glibenclamide0,43 mg/200 g of BW), and 1, 2, and 3 treatment groups (ethanol extract of seri leave 65, 130, dan 260 mg/kg of BW). Rats blood glucose level after induced intraperitoneally by alloxan130 mg/kg of BWcan be stated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
3
0
4
Order By: Relevance
“…Substance screening from M. calabura leaves showed alkaloid, flavonoid, tannin, saponin, triterpenoid, and steroid 13,14 Several previous studies stated that M. calabura leaf has potential as an antidiabetic drug, including a study by Zulham, Hendrarti, and Wahyuni (2019) 15 who showed that ethanol extract from M. calabura leaves with 50, 100, and 150 mg/kg obtained from macemiceion could reduce blood glucose level in alloxan-induced diabetic mice. The results from Herlina, Amriani, Solihah, and Sintya (2018) 16 also showed that ethanol extract from M. calabura leaves with 65, 130, and 260 mg/kg could reduce blood glucose levels to 28.90%, 32.16%, and 35.66% in male albino mice induced by alloxan.…”
Section: Introductionmentioning
confidence: 93%
“…Substance screening from M. calabura leaves showed alkaloid, flavonoid, tannin, saponin, triterpenoid, and steroid 13,14 Several previous studies stated that M. calabura leaf has potential as an antidiabetic drug, including a study by Zulham, Hendrarti, and Wahyuni (2019) 15 who showed that ethanol extract from M. calabura leaves with 50, 100, and 150 mg/kg obtained from macemiceion could reduce blood glucose level in alloxan-induced diabetic mice. The results from Herlina, Amriani, Solihah, and Sintya (2018) 16 also showed that ethanol extract from M. calabura leaves with 65, 130, and 260 mg/kg could reduce blood glucose levels to 28.90%, 32.16%, and 35.66% in male albino mice induced by alloxan.…”
Section: Introductionmentioning
confidence: 93%
“…Pada sebuah penelitian, dengan pemberian ekstrak air daun kersen pada hewan coba yang mengalami resistensi insulin dengan dosis 400 mg/kg BB dapat meningkatkan sensitivitas insulin, hal tersebut dibuktikan dari peningkatan nilai KITT yang serupa dengan kelompok yang diberikan glibenklamid [9]. Peningkatan nilai KITT disebabkan oleh kandungan flavonoid pada daun kersen yang dapat meningkatkan sensitivitas insulin dan mencegah kerusakan sel beta pankreas yang berfungsi untuk menghasilkan insulin [29].…”
Section: Meningkatakan Sensitivitas Insulinunclassified
“…Sirih (Piper betle) mengandung minyak atsiri yang efektif menghambat pertumbuhan Candida albicans (19) . Kersen (Muntingia calabura L) digunakan untuk menurunkan dula darah, hasil penelitian menunjukkan penurunan kadar dengan ED50 692.424 mg/kg (20) . Binahong (Anredera cordifolia Ten.)…”
Section: Pembahasanunclassified
“…Majalah Farmasetika menerima karya ilmiah di bidang farmasetika di alamat http://jurnal.unpad.ac.id/farmasetika/.N. S. Gunarti, Majalah Farmasetika, 6 (1) 2021,[14][15][16][17][18][19][20][21][22][23]…”
unclassified